The long gamma nail in the treatment of 329 subtrochanteric fractures with major extension into the femoral shaft - van Doorn, Ron; Stapert, Jouwert W. J. L. (The European journal of surgery, 2000)
Objective: To study the outcome of treating extensive proximal femoral fractures with the long Gamma nail. Design: Retrospective study, with a minimum follow‐up of a year. Setting: 24 hospitals throughout The Netherlands. Subjects: 329 patients with primary proximal femoral fractures. Main outcome measures: Functional results and complications. Results: 19 patients died in hospital and 6 were lost to follow‐up. Of the remaining 304 who were fully documented, 241 (80%) became fully mobile, 59 (19%) moderately mobile, and 4 remained bedridden. 264 patients had no pain, 38 had moderate pain and used oral painkillers, and 2 had severe pain that was difficult to treat. Major technical complications occurred in 17 patients: alignment and locking gave rise to most problems, 4 patients developed deep infections, and 7 patients needed additional measures before the fracture was solid. Conclusions: The long Gamma nail in the treatment of extensive proximal femoral fractures gave good functional results with acceptable rates of complications and union problems. Copyright © 2000 Taylor and Francis Ltd.